2007
DOI: 10.2478/s11532-006-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

The solvent extraction and spectrophotometric determination of vanadium (V) with 4-(2-thiazolylazo)resorcinol and tetrazolium salts

Abstract: Abstract:The formation and extraction of ion-associate complexes between the vanadium(V) -4-(2-thiazolylazo)resorcinol (TAR) anionic chelate and the cations of some mono-and ditetrazolium salts {3- (4,5-dimethyl-2-thiazol-tetrazolium] chloride (Tetrazolium blue chloride) and 3,3'-(3,3'-dimetoxy-4,4'-biphenylene)bis[2-(4-nitrophenyl)-5-phenyl-2H-tetrazolium chloride] (Nitro blue tetrazolium chloride)} have been studied. The optimum extraction conditions have been found. The composition of the V-TARmonotetrazoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 13 publications
(21 reference statements)
0
38
0
Order By: Relevance
“…However, some further investigations showed that this statement is not valid for IACs, which include NO 2 group(s) containing T m+ . 10,19,20 In fact, the values of β of such IACs are considerably lower than the expected ones according to literature. 11,18 Next step of investigation on the problem was to compare the values of β for IACs with T m+ , which differs only by the number of NO 2 groups (N nitro ).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, some further investigations showed that this statement is not valid for IACs, which include NO 2 group(s) containing T m+ . 10,19,20 In fact, the values of β of such IACs are considerably lower than the expected ones according to literature. 11,18 Next step of investigation on the problem was to compare the values of β for IACs with T m+ , which differs only by the number of NO 2 groups (N nitro ).…”
Section: Introductionmentioning
confidence: 62%
“…10,11,[18][19][20] Alexandrov et al 11,18 disclosed the first factor: the higher the molecular mass, the higher the association constant. However, some further investigations showed that this statement is not valid for IACs, which include NO 2 group(s) containing T m+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods such as ICP-MS, ICO-AES, NSAA, AAS, and spectrophotometry [6][7][8][9][10][11][12] are most frequently used for the determination of vanadium compounds. However, the relatively high instrumental cost and need for preconcentration, chromatographic separation, extraction or coprecipitation are common disadvantages.…”
Section: Artigo/articlementioning
confidence: 99%
“…TAR is widely known in inorganic analysis as a spectrophotometric reagent for the spectrophotometric determination of platinum [8] and transition [9][10][11] metals. TAR was used in ion-exchange liquid [12][13][14][15][16] and thin-layer [17] chromatography for the determination of metals ions in natural and drinking water as well as for electrophoretic determination of metals [18][19][20], in optical [21][22][23] and ionselective [24,25] sensors to determine the metals ions, for obtaining of the sorbents modified by azo reagent for concentration metals ions [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%